Dimerization of emission centers in Eu-doped GaN red light-emitting diode: cooperative charge capturing using valence states coupling. (14th November 2016) - Ishii, Masashi; Koizumi, Atsushi; Fujiwara, Yasufumi
Abstract: Despite the recent progress in red light-emitting diodes (LED) made of gallium nitride doped with europium (GaN:Eu) having sharp emission lines due to the 5 D0   →   7 F2 transition of Eu 3+, unexpected subsidiary Eu emission centers radiate several satellite lines. We investigated these subsidiary emission centers by analyzing the harmonic contents through electronic means, and observed the originally forbidden even harmonics in a specific frequency region of 23–45 MHz. The even-harmonic generation was formulized with a binary response caused by the electronic coupling of emission centers in valence states, i.e. dimerization. The coupling was consistent with the results of the optical analyses of former studies. The binary response was experimentally quantified by using a parameter such as the phase difference between the responses of coupled centers, and a significant phase difference of 63° was observed at 36 MHz. The injection charges were cooperatively captured by the coupled emission centers and were branched into the constituent centers for recombination, resulting in undesired satellite emission lines.